Alternative Dispute Resolution Dalam Sengketa Bisnis Internasional - Ronald Fadly Sopamena (Fakultas Hukum Universitas Pattimura, 2022)
Introduction: The importance of understanding international business contract law is because international business will involve more than one country so that the laws in these countries will also differ from one another. This will cause problems if there is a business dispute between two parties from different countries.Purposes of the Research: Thus, this study aims to analyze dispute resolution, especially alternative dispute resolution in international business.Methods of the Research: The research method used is normative juridical or what is known as legal research which is carried out by reviewing and analyzing the substance of the legislation on the subject matter or legal issue in its consistency with existing legal principles.Results of the Research: Choice of law is a consequence in an international business contract as a result of different legal rules in each country. Alternative dispute resolution is a method of dispute resolution that can be used in international business disputes. Arbitration, Mediation, Conciliation, Negotiation and Consultation can be used as initial options so that a solution can be obtained from the disputes faced before going through the litigation route which of course will be more time consuming and costly.